Genetic diversity analysis in muskmelon (Cucumis melo) for yield and quality traits - PRIYANKA, PRIYANKA; CHOUDHARY, SANTOSH; SINGH, BALRAJ (The Indian Journal of Agricultural Sciences, 2021)
In present study, 32 diverse genotypes of muskmelon (Cucumis melo L.) collected from different parts of the country were evaluated to study the correlation, path analysis and divergence for yield and quality characters using 18 morphological traits. In cluster analysis, genotypes were grouped into eight distinct clusters with a maximum of 13 genotypes in cluster I. The highest inter-cluster distance (355.14) was obtained between cluster V and VIII. Among the traits studied, shelf-life (54.23%), total soluble solids (27.82%) and fruit weight(7.26%) contributed a major share in the divergence of the genotypes. Four genotypes, viz. VRMM-315, VRMM- 12, Durgapura Madhu, and Jodhpur local accommodated into a single cluster, probably share a genetic similarity. The genotypes of cluster V (Punjab Sunehri, VRMM-205, VRMM-194) and cluster VIII (Jodhpur Local) being most divergent from others may serve as potential parents for breeding programmes.